Balladurette and Juppette: A Discrete Analysis of Scrapping Subsidies - Adda, Jérôme; Cooper, Russell (Journal of Political Economy, 2000)
0 TJJG 2OIILGG cXcccq tmo b&L&thMbpa unA pc dncucq mrjporij cxbjicij IDdunra2rou bwiuqcq iPi wii cLcqir